Community interventions with women’s groups to improve women’s and children’s health in India: A mixed-methods systematic review of effects, enablers and barriers - Desai, Sapna; Misra, Madhavi; Das, Aikantika; Singh, Roopal Jyoti; Sehgal, Mrignyani; Gram, Lu; Kumar, Neha; Prost, Audrey (BMJ, 2020)
India is home to over 6 million women’s groups, including self-help groups. There has been no evidence synthesis on whether and how such groups improve women’s and children’s health.